CONSTRUCTION OF RECIPROCAL VERBS IN ANGKOLA BATAK LANGUAGE - Harahap, Anna Leli (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
This research aims to analyze the syntactic aspects of reciprocal verb construction in the Angkola Batak language (ABl) using binding theory. A qualitative method with a descriptive approach is used in this research. Data were collected through literature study and the author's intuition as a native speaker, then analyzed by agih method and presented informally and formally. The result of the research identifies the formation process of reciprocal verbs in ABl through affixation, affixation+reduplication, and affixation+the word